It is useless to refrain the wave: the need for Brecht and Stanislavski in the hybridity of the epic theatrical forms of the Brazilian scene - Romano, Lucia [UNESP] (Taylor & Francis, 2020)
This article proposes to observe the relationship between the legacy of Constantin Stanislavski and Bertolt Brecht in Brazil, from the 1950s to the present, demarking the influences of both in the transformation of acting practices in the country as established from two moments: first, the construction of an inaugural epic mode of acting in the left-wing experience of the theatre company Teatro de Arena in São Paulo from 1953 to 1972; and second, the ”new” acting of performers in contemporary variations on a public, democratic, and experimental theatre in dialogue with the social and political dilemmas of Brazil, specifically in Cia Livre, Cia Bartolomeu, and Cia São Jorge. This analysis will enable us to discuss how the arrival of Brecht merged with the dissemination of Stanislavski’s newly introduced practices in the country, in a conjunction that led to the invention of a hybridized and particularly Brazilian way of acting. We will also examine how the re-emergence of a political theatre, after the slow reopening of the country in the late 1980s that succeeded the Brazilian Civilian-Military Coup in 1964, brought back the “need for Brecht” as well as the “need for Stanislavski”, both of which were embraced by the young artists of the national theatre without prejudice towards specific acting styles. Thereafter, we can glimpse contributions of what we consider to be the inherent plasticity of Brecht and Stanislavski’s legacies to the mutability of the art of acting.
Keywords: acting Practices; Brazilian theatre; contemporary scene; creative processes; Teatro de Arena